Fabrication of 2-layer flexible copper clad laminate by vacuum web coater with a low energy ion source for surface modification - Choi, H.-W.; Park, D.-H.; Choi, W.-K. (Korea Federation of Science and Technology, 2007)
In order to fabricate adhesiveless 2-layer flexible copper clad laminate (FCCL) used for COF (chip on film) with high peel strength, polyimide (PI; Kapton-EN, 38 μm) surface was modified by reactive O2+ and N2O+ ion beam irradiation. 300 mm-long linear electron-Hall drift ion source was used for ion irradiation with ion current density (J) higher than 0.5 mA/cm2 and energy lower than 200 eV. By vacuum web coating process, PI surface was modified by linear ion source and then 10-20 nm thick Ni-Cr and 200 nm thick Cu film were in-situ sputtered as a tie layer and seed layer, respectively. Above this sputtered layer, another 8-9 μm thick Cu layer was grown by electroplating and subsequently acid and base resistance and thermal stability were tested for examining the change of peel strength. Peel strength for the FCCLs treated by both O2+ and N2O+ ion irradiation showed similar magnitudes and increased as the thickness of tie layer increased. FCCL with Cu (200 nm)/Ni-Cr (20 mn)/PI structure irradiated with N2O+ at 1×1016/ cm2 ion fluence was proved to have a strong peel strength of 0.73 kgf/cm for as-received and 0.34 kgf/cm after thermal test.